Effect of Pressurized Irrigation Systems on Changing Some of the Soil Chemical Properties - Hamid Zare Abyaneh; Rasul Yousefi; Mehdi Jovzi; Abbas Abbasi; Masoud Shakarami (محیط زیست و مهندسی آب, 2021)
In recent years, due to limited water resources in Malayer plain, irrigation methods are changing from surface to under pressure. The purpose of this study was to investigate changes in soil quality due to changes in irrigation methods. For this purpose, 14 farms and 2 orchards equipped with sprinkler and drip irrigation system were selected and their soil quality changes compared with the corresponding values before implementation were evaluated by Mann-Whitney statistical test. Soil quality parameters included acidity (pH), nitrogen (N), phosphorus (P), organic matter (C), electrical conductivity of solutes (ECe) and potassium (K). The zoning map of the studied quality parameters was also prepared using ArcGIS software before and after the implementation of pressurized irrigation systems. The results showed that the difference between the values of the studied parameters before and after the implementation of pressurized irrigation systems including ECe, pH and C were non-significant at the level of 5% probability and the changes of P, K and N were significant. The results of measuring the qualitative parameters showed an increase in the mean values of pH, N, P and C from 7.72 to 7.80, 0.067 to 0.121 mg/kg, 11.01 to 17.95 mg/kg and 0.68 to 0.80%, respectively, compared with before the implementation of pressurized irrigation systems. However, ECe and K values of field soils decreased from 1.06 to 0.53 dS/m and 255.1 to 156 mg/kg, respectively. The results showed that changing the irrigation method reduced potassium and increased soil phosphorus and nitrogen.